Unraveling trends and disparities in acute myocardial infarction-related mortality among adult cancer patients: A nationwide CDC-WONDER analysis (1999–2020) - Humza Saeed; Uzair Majeed; Minahil Iqbal; Sufyan Shahid; Anum Touseef Hussain; Hammad Ahmad Iftikhar; Momina Riaz Siddiqui; Iftikhar Ali Ch; Salman Khalid; Naeem Khan Tahirkheli (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: Cancer patients are at an increased risk for the incidence and complications of acute myocardial infarction (AMI) due to shared risk factors and treatment-related adverse effects. Mortality trends for AMI-related deaths in adult cancer patients in the U.S. remain unexplored. Methodology: This study used CDC WONDER data for death certificates from 1999 to 2020, identifying U.S. adults (≥25 years) with cancer (ICD-10: C00-D49) who died of AMI (ICD-10: I21) as the underlying cause. Age-adjusted mortality rates (AAMRs) and annual percent changes (APCs) were calculated and stratified by gender, age, race, and geographic location. Results: Between 1999 and 2020, there were 109,462 AMI-related deaths in adult cancer patients. The AAMR decreased from 4.3 per 100,000 in 1999 to 1.4 in 2020. A significant decline occurred from 1999 to 2015 (APC: 6.65; 95 % CI: 6.95 to −6.40; p < 0.001), followed by a stable trend from 2015 to 2020 (APC: 1.36; 95 % CI: 2.69 to 0.91; p = 0.152). Men had higher AAMRs than women (3.5 vs. 1.5). AAMRs were highest in older adults (10.5) compared to middle-aged (0.7) and young adults (0.1). Racial disparities showed the highest AAMRs in non-Hispanic (NH) Black patients (2.7), followed by NH Whites (2.4), NH American Indian/Alaska Native (1.6), Hispanic/Latino (1.3), and NH Asian/Pacific Islander (1.1). Non-metropolitan areas had higher AAMRs than metropolitan areas (2.8 vs. 2.2). Conclusions: This analysis highlights a significant decline in AMI-related mortality among cancer patients in the U.S., with persistent disparities by gender, age, race and geographical location.